Beneath Clouded Hills: A More-Than-Human Approach to “Deep England” - Helle, Una (UnderCurrents: Journal of Critical Environmental Studies, 2025)
I’d like to tell you a story, ‘bout how England came to be… So begins a retelling of Des Grantz Geanz, a more-than-human origin tale of England (Birt & Helle, 2023), which recounts how thirty exiled giants were the first to appear on Albion’s shores, named so after the eldest. Here, they lived in harmony with the existing flora and fauna until the tyrant Brutus invaded and made them flee underground. The tale starts off Beneath Clouded Hills (Figure 1), an artist film by Verity Birt and myself, which forms part of a wider art and research project in which we explore the ambiguous term “Deep England” (Birt & Helle, 2023). [...]